Analysis Of The Impact Of Reverse Stock Split On Stock Trading Activity Of Pt. Bina Buana Raya National Shipping, Tbk And Pt. Bank Banten, Tbk - Wirawan, M Ananda Teri; Harahap, Lily Rahmawati; Aryanti, Rahmi; Naruliza, Esty (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Reverse stock split is a way for a company to increase the nominal value of shares by reducing the number of shares outstanding, this is usually done by companies that are experiencing problems and the stock price continues to fall which if left unchecked will result in delisting of shares in the capital market, this action in the eyes of investors can be interpreted as good news because it is considered an initial step to improve the company's fundamentals but this action is also sometimes interpreted as bad news because the company's management is considered to have failed to improve the company's fundamentals to the point of having to do a reverse stock split to maintain shares in the capital market. This study aims to determine the significance of the impact of reverse stock splits on stock prices and stock trading volume activity at PT.. Pelayaran Nasional Bina Buana Raya, Tbk and PT. Bank Banten, Tbk using the Trading Volume Activity method. This type of research is quantitative research. The data used in this study are secondary data using purposive sampling techniques. The results of the study using the Trading Volume Activity method show that stock mergers do not have a significant effect on stock trading volume activity, both from PT. Pelayaran Nasional Bina Buana Raya Tbk and PT. Bank Banten Tbk.. Because the companies that carry out stock mergers are companies that are experiencing difficulties in business and investors are less responsive if the information does not contain economic value.